Multiple thromboses in a late preterm infant present at birth. Issue 6 (7th June 2021) - Marriage, Thomas; Nair, Vrinda; Skeath, Thomas
Abstract : A late preterm infant was born to a diabetic mother on a background of reduced fetal movements and a poor CTG. It was noted immediately at birth that there was pathology in both upper limbs. Targeted investigation led to the diagnosis of bilateral upper limb arterial thromboses. Prompt assessment and multidisciplinary discussion led to an individualised management plan resulting in a positive outcome.